No Differences of Adolescents’ Hope in Terms of Developmental Phases and Gender - Ayriza, Yulia; Izzaty, Rita Eka (Bina Nusantara University, 2023)
The research aimed to investigate the differences in adolescents’ hope based on developmental phases (age) and gender. Hope, as one of the positive emotional resources, is essential for adolescents in performing psychosocial adaptations. There were still inconsistent results from several studies regarding differences in the level of hope in adolescence based on age and gender, which suggested the need for further investigation. This cross-sectional research involved 400 female and male adolescents who were attending junior and senior high schools with an age range between 13-20 years (M age= 16,04 years, 84% females and 16% males). Data were collected using Snyder’s Hope Scale, which was distributed to respondents through online Google Forms. The collected data were analyzed using the t-test techniques. The results show that most adolescents (45,8%) are in the very high category of hope. Further, the results also indicate that there is no significant difference in hope between early and late adolescents, as well as between girls and boys. This implies that interventions to improve adolescents’ hope can be carried out without paying attention to these demographic variables. Limitations and suggestions for future research related to the results are also discussed.